The role of governance mechanisms in improving administrative performance Applied Study in the Social Security Institution Benghazi (Economic studies journal, 2019)
The objective of this study was to identify the role of governance mechanisms in improving institutional performance and institutional performance by studying the institutions of the Social Security Fund in Benghazi city. It also aimed to identify the relative importance of governance mechanisms and their contribution to improving administrative performance, The application of governance mechanisms.The study population of all managers working in middle management level (of directors and heads of departments), the General Directorate of the Social Security Fund of Benghazi and the Social Security Fund east of Benghazi branch and a branch west of Benghazi's (60) participants, selected them a random sample size (40) participants. In this study questionnaire is used to collect data. The researcher used the test (Alpha Cronbach) for the extraction coefficient and consistency in the questionnaire, and descriptive statistics to know the answers to the participants, and statistical reasoning to test hypotheses of the study, Pearson correlation coefficient to find the relationship using the program Statistical Package for Social Sciences (SPSS)The results of the study showed that governance is an integrated system of control within the administrative institutions. There is a positive relationship between governance with its mechanisms of board of directors, internal audit, external auditing and performance improvement. There is also, relationship between the board of directors as one of the mechanisms of governance and administrativeperformance improvement. Between internal auditing as one of the mechanisms of governance and improving administrativeperformance. The results also showed that there is correlation between external auditing as one of the mechanisms of governance andadministrative performance improvement in the Benghazi Social Security Fund
Keywords: Governance; Administrative Performance; Social Security; Libya